A lady's guide to fortune-hunting - Irwin, Sophie (Pamela Dorman Books, Viking, 2022)
"A whip-smart debut that follows the adventures of an entirely unconventional heroine who throws herself into the London Season to find a wealthy husband. But the last thing she expects is to find love... Kitty Talbot needs a fortune. Or rather, she needs a husband who has a fortune. Left with her father's massive debts, she has only twelve weeks to save her family from ruin. Kitty has never been one to back down from a challenge, so she leaves home and heads toward the most dangerous battleground in all of England: the London season. Kitty may be neither accomplished nor especially genteel-but she is utterly single-minded; imbued with cunning and ingenuity, she knows that risk is just part of the game. The only thing she doesn't anticipate is Lord Radcliffe. The worldly Radcliffe sees Kitty for the mercenary fortune-hunter that she really is and is determined to scotch her plans at all costs, until their parrying takes a completely different turn.... This is a frothy pleasure, full of brilliant repartee and enticing wit--one that readers will find an irresistible delight"--